Pious Delinquents: Anticlericalism and Crime in Postrevolutionary Mexico. Issue 2 (15th June 2016) - Weis, Robert
Abstract : As Agent 15 of the Mexico City judicial police made his way home for lunch on a day early in December 1926, he saw a balloon floating in the breeze. He rushed to the rooftop observatorio of his apartment building, where he spotted a girl around 14 years old, wearing a lilac-colored dress, standing on a nearby roof and holding a string. Certain that the balloon had been released from this location, he ran down the stairs, and, while crossing the street, looked up to see yet another balloon. Balloons had been drifting through the sky since early morning, so many and from so many directions that police struggled to find where they were coming from. When the balloons popped, flyers came tumbling down, urging Catholics to engage in peaceful protest against government anticlericalism by adorning their houses with yellow and white stripes in honor of the Virgin of Guadalupe on her upcoming feast day, December 12. Accompanied by a beat policeman, Agent 15 approached two men in the building where he had seen the girl with the string, surmising that they had aided the launch. Although a search yielded nothing more incriminating than a stick with four strings, he arrested the men. He and other balloon-chasing police officers were obeying specific orders in hunting down the perpetrators that day, but in a broader sense they had become enforcers of laws introduced in the 1917 constitution that sharply restricted the scope of religious expression and observation in public.